Risk Factor Analysis for Dog Bite Victims in Davao City, Southern Philippines. - Evangelio, Sherelyn A.; Satur, Dejell Anne
Rabies, as one of the most serious bite-associated infectious diseases, kills 59,000 humans annually worldwide through the inoculation of rabid animal?s saliva into bite wounds or scratches. In the Philippines? Davao Region, over 200 human rabies deaths are recorded annually and the majority of the cases are associated with dog bites. This paper aims to identify the risk factors affecting the severity of rabies exposure of dog bites in humans in Davao City. Probit and logistic regression models are used to determine the association of rabies exposure with age and gender of the dog bite victim, location of the biting incident, ownership of the biting dog, and bitten location in the victim?s body. A total of 1,658 dog bite cases collected from the Davao City Health Office (CHO) are used in this study. The age of the dog bite victim and the bitten location in the victim?s body have significant effects on the severity of rabies exposure in both models. Results showed that the probability of getting exposed severely to rabies gets lower as the dog bite victim gets older. This finding can be observed in the data where the percentage of severe rabies exposure is highest at 0?4 yr old and dog bite incidence is highest at 5?14 yr old, both decreases as the person gets older. Moreover, dog bite victims bitten on the arm and/or hand, leg and/or thigh, and foot are less likely to be severely exposed to rabies than those who are bitten in other parts of the body. These results suggest that the involved authorities should strengthen information, education, and communication (IEC) campaigns targeting parents with toddlers and in pre-schools and elementary schools. Furthermore, prompt medication ? including first aid treatment ? is advised when bitten by a dog.